Perkembangan Pasar Paninggahan Kecamatan Junjung Sirih Kabupaten Solok Tahun 1990-2018 - Fiendra, Nikra Fadhila; Najmi, Najmi (Jurusan Sejarah FIS UNP, 2024)
ABSTRACT This research discusses Paninggahan Market, which is one of the traditional markets in Nagari Paninggahan, Jujung Sirik District, Solok Regency from 1990-2022. The focus of the study is to discuss the development of the Paninggahan Market. The aim of this research is to reveal the background to the emergence of Paninggahan Market in Paninggahan, the development of Paninggahan Market from 1990-2022. This research includes historical qualitative research, using historical methods in the form of library studies, archives and interviews. From the discussion it can be seen that, First, one of the traditional markets of Nagari Paninggahan is Paninggahan Market. Paninggahan Market is in Solok, West Sumatra, Indonesia, on Jalan Raya Paninggahan - Malalo. Paninggahan Market was originally just a small hall around Jalan Gando which did not have a stall or stall that could accommodate traders. Traders usually come from local residents and people from outside Paninggahan, such as Sumani, Muaropingai, Saniang Baka, and Singkarak. This market, which was built based on complaints from the community, eventually developed into a fairly large market in the Junjung Sirih District area. Second, Paninggahan Market continues to grow, and this increase has an impact on the activities and survival of the people of Nagari Paninggahan directly and indirectly. This is characterized by observable changes in the socio-economic and socio-cultural fields, which are symptoms that can be found in every society